Faktor-Faktor Yang Mempengaruhi Eektivitas Metode Flipped Classroom Dalam Pembelajaran Bahasa Asing: Narrative Review - Irfan (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study aims to analyze the factors that influence the effectiveness of the Flipped Classroom (FC) method in foreign language learning. The method used in this study is a narrative review, which examines various studies related to the application of FC in the context of foreign language learning. This study identifies the main factors that influence the success or failure of FC, such as technological readiness, student skills, teacher readiness, and social and cultural factors. The results of the study indicate that FC can improve students' speaking and foreign language comprehension skills, but its effectiveness is highly dependent on the availability of technology, student readiness in using digital technology, and teaching skills. This study recommends that educators be given further training in using technology to support FC-based learning, as well as the need for adjustments to the local context and student needs to optimize its implementation.